2018
DOI: 10.3892/ol.2018.8212
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for critical role of Tie2/Ang1 interaction in metastatic oral cancer

Abstract: Abstract. Angiopoietin-1 (Ang1) is a binding partner of endothelial cell-specific tyrosine-protein kinase receptor (Tie2), which serves important roles in vascular development and angiogenesis. Tie2 is closely associated with the metastasis of oral squamous cell carcinomas (OSCCs) however, little is known about the correlation between Tie2 and Ang1. In the present study, the functional mechanisms of the Tie2/Ang1 interaction were investigated using Tie2 overexpressed (oeTie2) OSCC cells and recombinant Ang1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…37 Experimental study recently demonstrated that an in-vitro treatment with angiopoietin-1 for Tie2-overexpressed oral squamous cell carcinoma cells enhances the cell-cell and cellextracellular matrix adhesive activities of cancer cells. 38 This nding indicates that angiopoietin-1 directly up-regulates the functional activity of Tie2. In our study, the angiopoietin-1 plasma level was decreased after surgical resection, which may subsequently suppress the tyrosine phosphorylation level of Tie2 in erythrocyte membrane.…”
Section: Discussionmentioning
confidence: 87%
“…37 Experimental study recently demonstrated that an in-vitro treatment with angiopoietin-1 for Tie2-overexpressed oral squamous cell carcinoma cells enhances the cell-cell and cellextracellular matrix adhesive activities of cancer cells. 38 This nding indicates that angiopoietin-1 directly up-regulates the functional activity of Tie2. In our study, the angiopoietin-1 plasma level was decreased after surgical resection, which may subsequently suppress the tyrosine phosphorylation level of Tie2 in erythrocyte membrane.…”
Section: Discussionmentioning
confidence: 87%
“…Tie2 is a receptor tyrosine kinase expressed principally on vascular endothelium and interacts with its ligand angiopoietin-1 and angiopoietin-2 in regulating vessel branching and maintaining endothelial homeostasis [ 36 ]. Experimental study recently demonstrated that an in vitro treatment with angiopoietin-1 for Tie2-overexpressed oral squamous cell carcinoma cells enhances the cell-cell and cell-extracellular matrix adhesive activities of cancer cells [ 37 ]. This finding indicates that angiopoietin-1 directly upregulates the functional activity of Tie2.…”
Section: Discussionmentioning
confidence: 99%
“…Having identified a link between Ang1 and ARP2/3, we further evaluated the signaling pathway involved in Ang1-dependent ARP2/3 expression. Ang1 is known as a Tie2 agonist, which promotes phosphorylation of Tie2 to activate its downstream pathways [27,28]. Tie2 was initially found to be overexpressed in tumour vessels, while recent studies reported Tie2 expression in cancer cells [17,29].…”
Section: Ang1 Regulates Arp2/3 Expression Through Tie2-pi3k/akt Pathwaymentioning
confidence: 99%